ショウワキチ デ カンソク サレル ゴゼンガワ Pc5 チジキ ミャクドウ ノ ヘンパ シュジク ホウコウ ノ トクイセイ - 加藤, 賢一; カトウ, ケンイチ; Kato, Ken-ichi (1996)
P(論文) 南極昭和基地で観測される午前側Pc5地磁気脈動のH-D成分間の偏波は顕著な特異性を示す。他の観測点の偏波主軸が一般的に磁気北東方向を指すのに対し, 昭和基地の偏波主軸は磁気北方向を指す。本研究では, 昭和基地を含め昭和基地から数10km離れた二つの観測点と数100km離れた二つの観測点で同時観測された地磁気変化データから, 昭和基地で現れる午前側Pc5脈動の偏波主軸方向の特異性を明らかにすることが目的である。その結果, 以下のことが明らかとなった。1) 午前側Pc5脈動の偏波主軸方向の特異性は, 昭和基地近傍で顕著に現われ, 時刻に依存しない。2) その特異性はH-D成分間の振幅比よりも位相差の変化の影響を受けている。特にD成分の位相変化による。3) 昭和基地で現われる位相変化は, H成分で10°の進み, D成分で30°の遅れを持つ。これらの特性を持つ可能性として, 昭和基地で観測されるPc5脈動の偏波主軸方向の特異性の原因は, 昭和基地近傍における不均質な地下誘導電流の局所的な効果によるものと推論される。 Pc5 geomagnetic pulsations observed in local morning at Syowa Station (SYOW) often show anomalous polarization characteristics in the horizontal plane. The sense of polarization of Pc5 pulsations observed at SYOW is the same as that at the other stations in the southern polar region. The orientation of the main polarization axis at SYOW points to geomagnetic north, that at other stations to the geomagnetic northeast. The purpose of this study is to explain the anomaly in the orientation of the polarization axis of morning side Pc5 pulsations at SYOW and four stations near SYOW, two of which are located tens of km away from SYOW and hundreds of km from the other two antarctic stations. The results are as follows : 1) The anomaly in the orientation of polarization axis of Pc5 pulsations is large at SYOW with no local time dependence. 2) The anomaly is related to the difference in the phase of the H and the D components. It is especially affected by the phase variations of the D component. 3) The phase of the H component of Pc5 pulsations at SYOW shows about 10°lead and that of the D component about 30°lag. It is inferred that the origin of the anomaly of the orientation of polarization axis of Pc5 pulsations at SYOW is caused by a local effect due to inhomogeneous electric currents induced underground around SYOW. departmental bulletin paper